Bus selection index for distributed generators placement and sizing in the electrical network - Muhammad Raza; Aurangzeb Rashid Masud; Ayaz Hussain; Ravi Mohan Lal (Automatika, 2023)
Renewable energy sources, widely considered as distribution generation units, will be essential parts of the future electrical network. They will be integrated into the network at all voltage levels and act as the main controlling elements in the microgrid to stabilize the network. However, the objective of determining the suitable busbar to integrate the renewable generation source and its maximum capacity is still an indecisive problem. This article presents a methodology to select suitable busbars to integrate the renewable generation unit. A bus selection index is proposed based on three criteria, i.e. voltage deviation, active power loss, and grid energy infeed. The developed algorithm considers network busbar voltage limit and branch loading as constraints and the solution is determined using analytical technique. Algorithm is implemented in MATLAB, and MATPOWER is used for the power flow analysis. Furthermore, the proposed methodology is analysed on CIGRE and IEEE medium voltage benchmark network.